Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
Keywords: Bibliographie